STRATEGI KEHIDUPAN KELUARGA MISKIN (STUDI KASUS KELUARGA PETANI) DI DESA LAMAWARA, KECAMATAN ILE APE, KABUPATEN LEMBATA - Langobelen, Hermina Ose; Adang Djaha, Ajis Salim; Pandie, Ardy Y. (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Lembata Regency is one of the regencies that still experiences poverty problems. Poverty is one of the causes of welfare problems in society in the form of conditions of inability to fulfill basic needs. The life of the village community is still below standard due to the low income capacity to meet basic needs in the form of food, clothing, and shelter. This low income capacity will also have an impact on reducing the average standard of living such as public health standards and children's education standards. This study aims to determine the Strategy of Farming Families to get out of the cycle of poverty in Lamawara Village, Ile Ape District, Lembata Regency. The method used in this study is a qualitative method with a phenomenological approach. The phenomenological approach is related to understanding the daily life and intersubjective world (life world) of participants. The poor farming family of Mr. Antonius Tena tries to meet their daily needs by relying on working in the garden to plant corn and eggplant vegetables to sell at the market to meet their life needs. The survival strategy is a manifestation of rational choice actions carried out by poor families, responding to various situations faced either through efforts such as utilizing mutual help (family and neighbors), joining arisan networks, maintaining good relations with co-workers and bosses, and husband and wife working part-time. The agricultural sector has an important meaning for the lives of farmers in improving their businesses. This means that the better the life of the farming family, the better it will affect the improvement of their family's welfare. In the socio-economic life of farming families, namely from the aspect of farming efforts, mental attitude aspects, education aspects and income aspects directly affect the standard of living of the farming family community.